Configuration and dimension optimization of active power Filter in distribution networks using a Multi-Strategy improved algorithm - Bo, Tang; Haidong, Liang; Xiwen, Yue; Ruijin, Zhu (International journal of electrical power & energy systems, 2025)
•Introducing a multi-strategy BWO algorithm for optimal APF configurations.•This paper minimizes installation, maintenance costs, & harmonic transmission.•Validated on the IEEE 18-bus system, reduces costs while meeting standards.•This paper offers an innovative approach to optimize APF configurations. With the growing integration of electric vehicles, smart grids, and power electronics in power systems, harmonic distortion is becoming a pressing concern, degrading power quality and causing equipment issues that may lead to grid failures. Active Power Filters (APF) are extensively used in the field of harmonic suppression to proactively compensate for grid distortion caused by harmonic variations. In order to optimize the layout and capacity of APF connected to the grid, this paper proposes a hybrid Improved algorithm for the economic optimization of APF configurations. Initially, based on Beluga Whale Optimization, a multi-strategy Improved algorithm is introduced, and through verification on benchmark test functions, this method effectively improves convergence speed and accuracy. Subsequently, to achieve economically optimal conditions while meeting IEEE 519 standards, IBWO is employed to search for the installation positions and capacities of APF. Through practical validation, the Total Harmonic Distortion (THD) of each bus before APF installation exceeds 5%, and after optimization configuration, the THD of each bus falls below 5%. This significantly reduces grid distortion, meeting the standards for grid operation. The proposed method effectively ensures the safe and stable operation of the grid and equipment while providing reference for economically efficient configurations in other domains.